Karawitan Composition of "Siwa Lingga" | Komposisi Karawitan “Siwa Lingga" - I Made Dwi Permana; I Gede Mawan (GHURNITA: Jurnal Seni Karawitan, 2023)
And Linga in Sanskrit means a sign, while in Balinese it is interpreted as Linggih, so the author can conclude that Shiva Linga is a place to worship, respect and seek Lord Shiva. The purpose of this work is to realize an idea, a concept that has been thought out and as a place to increase experience in the field of creating works of art, especially in the field of musical art. In realizing this work, it is done by adopting the method described by Alma M. Hawkins in his book Creating Through Dance, that the creation of a work of art is taken through three stages, namely, exploration, improvisation and formation.